2021
DOI: 10.1017/s0007114521002488
|View full text |Cite
|
Sign up to set email alerts
|

Gluten contamination in labelled gluten-free, naturally gluten-free and meals in food services in low-, middle- and high-income countries: a systematic review and meta-analysis

Abstract: The gluten-free diet is based on the consumption of foods without gluten, which aims to manage celiac disease. The concern of celiac patients is that these foods should be safe. However, gluten contamination can affect these foods. The objectives of this review and meta-analysis were first, to identify articles that detected gluten contamination in gluten-free foods using validated methods. Second, to quantify the overall prevalence of gluten contamination of naturally gluten-free foods, labelled gluten-free p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In Italy, gluten‐free pizzas bought at certified restaurants 70 and regular restaurants 71 were both below 20 mg/kg. Naturally, gluten‐free meals were more likely to cross‐contact with gluten than meals labeled gluten‐free 68 . In US restaurants, 1% 65 and 25% 72 of gluten‐free foods fried in the same fryer as gluten‐containing foods had a gluten content >20 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, gluten‐free pizzas bought at certified restaurants 70 and regular restaurants 71 were both below 20 mg/kg. Naturally, gluten‐free meals were more likely to cross‐contact with gluten than meals labeled gluten‐free 68 . In US restaurants, 1% 65 and 25% 72 of gluten‐free foods fried in the same fryer as gluten‐containing foods had a gluten content >20 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of hazardous gluten content in products sold as gluten‐free varies between studies in different countries: 6% in Australia, 66 10% in Ireland 67 (the majority >100 mg/kg), 0% in Italy 60 . Since 2009, the prevalence of gluten cross‐contact in food services reported in the scientific literature has decreased, to overall 2.93% (95% confidence interval 1.60%, 4.91%) 68 . In countries where a rigorous legislation is not in place, or that do not have the obligation to inform customers on allergens in foods, 65–68 the prevalence of hazardous gluten cross‐contact seems to be more prevalent than in the EU.…”
Section: Resultsmentioning
confidence: 99%
“…The successful application of the “Purity Protocol” has shown that is indeed possible to produce safe oats in compliance with the legislation and suitable for celiac patients on gluten-free diet ( 23 ). Thus, although there is robust evidence indicating that oats are indeed frequently contaminated ( 15 , 22 , 24 ), at the same time improving the practice of using special gluten-free oats cultivars and supervision of oat production and manufacturing appears as a potent line of action to obtain good, safe products.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the results from Bustamante et al (2017) showing that the level of gluten contamination in cereal based CGF and PWG has decreased in the period from 1998 to 2016. In addition, Guennouni et al (2021) found that the prevalence of gluten contamination in all types of gluten free foods decreased between the time periods 2000-2008 and 2015-2020. In food allergy risk assessment, it is assumed that if an allergic person includes a product in the diet, the amount consumed is the same as in the general population. We made the same assumption in this study and used data from the Danish national food survey grouped to be suitable for food allergy risk assessment (Birot et al, 2017).…”
Section: Tablementioning
confidence: 98%